Carbon-containing additives changes the phosphorus flow by affecting humification and bacterial community during composting. (July 2023) - Li, Shuxin; Xu, Shaoqi; Chen, Shuo; Zhang, Hao; Zhan, Yabin; Jia, Kaixue; Cheng, Meidi; Wei, Yuquan
Graphical abstract: Highlights: More P transformation from total IHP to orthophosphate with humus in T1 and T3. Glucose enhanced composting ALP and initial ACP activity compared to other additives. Composting humus in T1 bind to AP and phosphatase better than that from woody peat. Lentibacillus was a key carbon cycle bacteria in mature phase affected by additives. Phosphatase enzyme and humus had 59.8% contribution to composting P forms dynamics. Abstract: Phosphorus recycling from organic wastes to prepare a fertilizer by composting is promising. The aim of this study was to compare the effect of diverse carbon-containing additives (T1, glucose; T2, biochar; T3, woody peat) on phosphorus (P) fractions transformations, humus formation and bacterial community succession in chicken manure composting. Results showed that orthophosphate monoester was significantly related to the humification process, and glucose or woody peat addition increased the P in humus. Lentibacillus was a key carbon cycle bacteria related to organics stabilization affected by carbon-containing additives. Redundancy analysis and variation partitioning indicated that phosphatase enzyme activity driven by bacterial community and humic substance had 59.7% contribution to P fractions dynamics. The findings highlight an efficient humus-regulation P stabilization way, notably in composting adding glucose to form humus with a better binding ability to labile P forms and phosphatase.